Enhancing supply resilience in the COVID-19 pandemic: A case study on beauty and personal care retailers - Md. Tarek Chowdhury; Aditi Sarkar; Pronab Kumer Saha; Rakib Hasan Anik (Modern Supply Chain Research and Applications, 2020)
Purpose The COVID-19 pandemic interrupts the supply chain of products around the world. The supply chains of beauty and personal care products in Bangladesh are also heavily interrupted during this pandemic. While these products are perceived as essential by mass people, retailers are struggling to get the supply of the products and maintain a smooth delivery to the people. Considering such facts, the purposes of the study are to identify how the supply of retailers of these products is interrupted and how they can overcome the interruptions to ensure supply resilience. Design/methodology/approach A case study method has been used in this study. The data has been collected through interviews from 16 retailers of beauty and personal care products. Findings The results show that the supply of retailers of beauty and personal care products is interrupted in several ways. These include product shortage, limited delivery service, interruption of supplier payment, limited credit facility and irregularity in product delivery. To minimize the impacts of the interruptions and enhance supply resilience, retailers can undertake several strategies including intensive interactions and developing cooperation with the distributors and manufacturers, ordering bulk quantity, formulating an adjusted credit ratio and focusing on product availability over brand preference. Research limitations/implications The context of this study is limited to the beauty and personal care products of Bangladesh. Further study can be conducted in other countries and also supply chains of other products to enhance the generalizability of the findings of this study. Practical implications Supply interruptions are identified, and strategies are suggested to ensure the supply resilience of retailers of beauty and personal care products. If proposed strategies are implemented by retailers of these products, supply interruptions can be minimized. Originality/value The study contributes to the knowledge of the retail supply chain during a pandemic. It also contributes to the supply management and resilience of retailers. As the context is a developing country, the study also contributes to the literature on developing countries.
Keywords: 650; Beauty and personal care retailers; COVID-19; Supply chain interruptions; Supply resilience